Seroprevalence of Scrub typhus in a rural tertiary care hospital of Eastern India - Saswati Chattopadhyay; Nabamita Chaudhury; Tanusri Biswas (Asian Journal of Medical Sciences, 2022)
Background: Scrub typhus is a Rickettsial infection caused by a gram-negative intracellular bacillus Orientia tsutsugamushi. It is an important cause of pyrexia of unknown origin (PUO). The infection is spread by the larval form of a mite–Trombiculid soft mite and is called ‘chiggers’. The infection affects man accidentally. Aims and Objectives: The study was done to find the sero-prevalence of the infection in patients with high fever not responding to any treatment. Materials and Methods: The study was conducted for 1 year (January 2021 to December 2021 in patients of all ages and sexes complaining of high fever and body ache with/without seizures and change in mental status. The serum samples were subjected to immunoglobulin M enzyme linked immunosorbent assay for Scrub typhus after excluding the other causes of the common febrile illnesses such as Malaria, Japanese encephalitis), chikungunya, dengue, typhoid and leptospirosis. Results: The seroprevalence of Scrub typhus in this study period was 39.74 % amongst the 761/1915 positive samples. Maximum number of positive cases were noted in the cooler months of the year – November 2021 (192 cases; 25.23%) followed by December (142; 18.66%). Of all the positive cases, maximum 396 (78%) were found in patients residing in the rural areas of the Purba Burdwan district. Furthermore, the maximum number of cases was found in the age group 0-10 yrs—463 (60.84%) but a very slight male predominance. No mortality, however, was reported. Conclusion: Scrub typhus is an emerging infection and early treatment can save many lives.